Identification and Characterization of Five Cold Stress-Related Rhododendron Dehydrin Genes: Spotlight on a FSK-Type Dehydrin With Multiple F-Segments - Wei, Hui; Yang, Yongfu; Himmel, Michael E.; Tucker, Melvin P.; Ding, Shi-You; Yang, Shihui; Arora, Rajeev (Frontiers in Bioengineering and Biotechnology, 2019)
Dehydrins are a family of plant proteins that accumulate in response to dehydration stresses, such as low temperature, drought, high salinity, or during seed maturation. We have previously constructed cDNA libraries from Rhododendron catawbiense leaves of naturally non-acclimated (NA; leaf LT50, temperature that results in 50% injury of maximum, approximately -7 oC) and cold-acclimated (CA; leaf LT50 approximately -50 oC) plants and analyzed expressed sequence tags (ESTs). Five ESTs were identified as dehydrin genes. Their full-length cDNA sequences were obtained and designated as RcDhn 1-5. To explore their functionality vis-à-vis winter hardiness, their seasonal expression kinetics was studied at two levels. Firstly, in leaves of R. catawbiense collected from the NA, CA, and de-acclimated (DA) plants corresponding to summer, winter and spring, respectively. Secondly, in leaves collected monthly from August through February, which progressively increased freezing tolerance from summer through mid-winter. The expression pattern data indicated that RcDhn 1-5 had 6- to 15-fold up-regulation during the cold acclimation process, followed by substantial down-regulation during deacclimation (even back to NA levels for some). Interestingly, our data shows RcDhn 5 contains a histidine-rich motif near N-terminus, a characteristic of metal-binding dehydrins. Equally important, RcDhn 2 contains a consensus 18 amino acid sequence (i.e., ETKDRGLFDFLGKKEEEE) near the N-terminus, with two additional copies upstream, and it is the most acidic (pI of 4.8) among the five RcDhns found. The core of this consensus 18 amino acid sequence is a 11-residue amino acid sequence (DRGLFDFLGKK), recently designated in the literature as the F segment (based on the pair of hydrophobic F residues it contains). Furthermore, the 208 orthologs of F-segment-containing RcDhn 2 were identified across a broad range of species in GenBank database. This study expands our knowledge about the types of F-segment from the literature-reported single F-segment dehydrins (FSKn) to two or three F-segment dehydrins: Camelina sativa dehydrin ERD14 as F2S2Kn type; and RcDhn 2 as F3SKn type identified here. Our results also indicate some consensus amino acid sequences flanking the core F-segment in dehydrins. Implications for these cold-responsive RcDhn genes in future genetic engineering efforts to improve plant cold hardiness are discussed.